Análisis de escenarios para mitigar el riesgo de Triquinelosis humana debido al consumo de embutidos crudo curados en Santa Fe, Argentina - Sequeira, G.J. (2020)
Trichinellosis is a zoonotic disease caused by Trichinella spiralis with endemic presentation in Argentina associated with subsistence pig production. The objective of this work was to evaluate the impact of the adoption of three hypothetical risk management measures on the risk that consumers suffer Trichinellosis in the province of Santa Fe due to the consumption of meat sausages without official control. A scenario analysis was performed based on a previously quantitative risk assessment and the management measures were selected to reduce and increase clandestine breeding of pigs and decrease the prevalence of the parasite in pigs. Based on the baseline risk model of 103 cases of Trichinellosis per year in the province of Santa Fe, by reducing clandestine breeding of pigs between 20-50 %, would be 44 average cases and if, on the contrary, clandestine breeding would increase between 100-150 %, the number of annual cases expected would be 506. If the prevalence of pigs positive for T. spiralis is reduced by 50 %, the number of annual cases would be 52. These results provide information for the selection of interventions based on science to reduce risk in the population.